Essays on macrofinance applied to U.S. - Santos, Davi Albuquerque Vieira dos (2025)
This thesis aims to better understand the directionality of relationships of economic variables using data for the United States and new techniques that help unwrap the qualitative aspects of these relations, making two distinctive empirical exercises. On the first essay, we address instrumentalized co-movements across time/frequencies between macro-finance variables and household credit decisions, using consumer loans and mortgage data, and its respective delinquency rates in U.S. Methodologically, we use partial wavelet coherency, partial phase-difference diagram and partial regression coefficient. We find that oscillations at different frequencies of growth and delinquency rates for credit variables may have different impacts on real return on stock indices, as well as, on the growth of real income, wealth, and consumption expenditures. On the second essay, the conditional growth connectedness between U.S. and the remaining G10 economies from 1996 to 2023 is addressed. We measure time varying external spillover effects under different economic conditions. We highlight the role played by France and Russia in the second half of the 90s, and by the G7 (except for U.S.) and the Eurozone countries after the pandemic. Regarding the instruments, we use a representative set of macroeconomic variables useful to draw insights on transmission channels. We find that high levels of debt to GDP and interest rates in U.S. are relevant after the pandemic. Our findings are useful to draw public policies to safeguard financial stability and to analyze financial crisis drivers. The simultaneous variation of statistics along time and frequencies allow us to detect new stylized facts about the last three decades of U.S. financial development and economic growth, like the role played by growing public debt and interest rates.